Pertanggungjawaban Pidana Korporasi dalam Pelanggaran Hak Asasi Manusia yang Berat - Mahrus Ali (Fakultas Hukum Universitas Islam Indonesia, 2011)
This research focuses on corporate criminal liability for gross violation of human rights. Based on normative legal research, this research reveals; first, extending criminal responsibility beyond individual to corporation for gross violation of human rights is required because national states are sometimes unwilling or powerless to properly sanction corporations for fear of negative economic consequences. Corporation also results serious or systematic human rights violations and encourages criminal conduct by maintaining a corporate culture that condones or even rewards violations of the law; second, Canada and Australia have opened a prosecutorial window by suing Unocal and Anvil Mining Limited as the perpetrator of crime against humanity; last, In Indonesia prosecuting corporation for human right violations will resulted into reformulation of criminal conduct of abetting, limitation of corporate responsibility and punishment and treatment.Key words : Corporation, criminal responsibility, gross violation of human rights